Comparison of Real and Forecasted Domestic Hot Water Consumption and Demand for Heat Power in Multifamily Buildings, in Poland - Wojciech Rzeźnik; Ilona Rzeźnik; Paweł Hara (Energies, 2022)
Determining the demand for heat power for domestic hot water preparation is necessary to perform a building energy assessment. For this, we need to predict domestic hot water consumption. Considering the number of factors influencing domestic hot water consumption, it is difficult to develop a highly accurate methodology. The aim of the study was to compare the real domestic hot water consumption and heat power for its preparation with the values calculated based on the available prediction methods in multi-family buildings. The analysis was carried out based on annual monitoring (2021 year) of domestic hot water consumption and the actual demand for heat power in eight multi-family buildings located in Grudziądz, in Central Poland. The results of these measurements were compared with the values determined based on the available methodologies for forecasting the demand for heat power and domestic hot water consumption: Sander’s, Recknagel’s, the standard method and the method according to Polish regulations from 2008 and 2015. The real average demand for heat power for domestic hot water was 89.8 ± 8.5 W/person, 211.2 ± 13.7 W/apartment and 4.8 ± 0.3 W/m2, and the daily domestic hot water consumption was 26.7 ± 3.6 dm3/person·day, 62.6 ± 5.8 dm3/apartment·day and 1.4 ± 0.1 dm3/m2·day. The real demand for heat power for domestic hot water was lower than that determined by the analyzed methods. The values obtained from the modified standard method based on Standard PN-92/B-01706/A1: 1999, with mean relative error of 10.5 ± 4.1%, were the closest to the real values. The current ordinance method (Regulation 2015) is characterized by an error of 45.4 ± 10.2%. The predicted domestic hot water consumption using the current ordinance was the closest to the real consumption. On average, it was higher by 7.7 ± 5.0%.